Prevalence of and Risk Factors for Cognitive Impairment Among Elderly Without Cardio- and Cerebrovascular Diseases: A Population-Based Study in Rural China - Ren, Li; Bai, Lingling; Wu, Yanan; Ni, Jingxian; Shi, Min; Lu, Hongyan; Tu, Jun; Ning, Xianjia; Lei, Ping; Wang, Jinghua (Frontiers in Aging Neuroscience, 2018)
This study aimed to evaluate the prevalence of cognitive impairment and the distribution of its risk factors among residents aged ≥60 years without cardiovascular and cerebrovascular diseases in rural areas of northern China screened with the Chinese version of the Mini-Mental State Examination (MMSE). Between 2012 and 2013, a questionnaire survey was conducted to collect basic information from participants. Cognitive function was assessed using the MMSE. In the univariate analysis, risk factors for cognitive disorders were female sex, low education, and central obesity, while drinking was found to be a protective factor. In the multivariate analysis, risk factors were old age (odds ratio [OR], 1.888; 95% confidence interval [CI]: 1.256–2.838; P = 0.002 for the 70-year-old group compared with the 60-year-old group; OR, 3.593; 95% CI, 2.468–5.230; P<0.001 for the ≥75-year-old group compared with the 60-year-old group), low education (OR, 3.779; 95% CI: 2.218–6.440; P<0.001 for the illiterate group compared with the group with ≥9 years of education; OR, 1.667; 95% CI, 1.001–2.775; P=0.05 for the group with less than primary school compared with the group with ≥9 years of education), and higher blood pressure (OR, 1.655; 95% CI: 1.076–2.544; P=0.002 for individuals with stage III hypertension compared with those with normal blood pressure). These findings suggest that it is crucial to manage and control level of blood pressure, and improve educational attainment in order to reduce the prevalence and burden of cognitive impairment among low-income residents in rural China.